The effect of midsole thickness on running economy, spatiotemporal values and perceptions of comfort and exertion in well-trained runners: A randomized, cross-over trial - Baumann, G.-A.; Biedermann, K.; Item, E.; Spengler, C. M.; Beltrami, F. G. (Sports Medicine - Open, 2025)
Background Distance running has been revolutionised by the introduction of modern running shoes, named advanced footwear technology (AFT). AFT shoes commonly implement carbon fibre plates to increase longitudinal bending stiffness as well as highly responsive midsole foams, which increase energy return. In 2022, World Athletics stipulated that midsoles in competition road running shoes cannot exceed 40 mm in thickness, but this limit seems arbitrary. Therefore, this study aimed to understand the effect of midsole thicknesses in AFT shoes at (40 mm) and above (50 mm) the current regulation on running economy (RE), perceived comfort and exertion, and spatiotemporal variables during treadmill and overground (400-m track) running, while comparing values to those of an entry level running shoe (EL).